The tourism area life cycle review, relevance and revision (Aspects of tourism, 2024)
"The Tourism Area Life Cycle model has been cited and used by academics and those in the industry for over 40 years. This book provides an overview of the contribution of the model, its strengths and weaknesses, and particularly its relevance in the 21st century. The final section considers revisions and concludes with a new version of the model"--